การย่อยร่วมแบบไม่ใช้ออกซิเจนของมูลสุกร ใบปาล์ม และขยะของแข็งชุมชนในถังปฏิกรณ์ร่วม 2 ขั้นตอนและถังปฏิกรณ์เมมเบรน - อัญชลี แท่นนิล (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
This research investigated the methane production and wastewater treatment efficiencies in anaerobic co-digestion of pig manure and food waste as well as of pig manure and palm leaf. The studied ratios were varied at 100:0, 90:10, 80:20 and 70:30 with TS contents of 5%, 10% and 20% in combined two stage reactor and membrane reactor. It was found that the membrane reactor provided better treatment efficiencies than the combined two stage reactor but the difference in methane production was not significant. Increasing the food waste ratios and the total solid contents, the methane production was increased. The methane portion and methane production in membrane reactor at 70:30 ratio and 20%TS were 59.6% and 1.57±0.12 L/d, respectively. The treatment efficiencies in term of COD, TS and VS removal were 87.5±0.9%, 47.1±1.3% and 49.7±1.9%, respectively. Using palm leaf as co-substrate at 70:30 ratio and 20%TS, the obtained performances in membrane reactor were 60.5 %, 0.86±0.09 L/d, 91.7±0.7%, 52.2±2.7% and 43.2±1.3%, respectively